RESIDENTIAL BUILDINGS BUILT BEHIND THE STATE INDUSTRY BUILDING (DERZHPROM) IN THE LATE 1920S AND EARLY 1930S: BLOCKS EAST OF NAUKY AVENUE - Gella О.; Didenko, K. (Municipal economy of cities. Series: «Economy science», 2024)
The article is devoted to residential buildings built in the late 1920s and early 1930s in the metropolitan Kharkiv, in the area behind the State Industry Building (Derzhprom) east of Nauky Avenue. The design andconstruction of these residential neighbourhoods, which took place between 1926 and the late 1930s and had their peculiarities and diversity, are not sufficiently covered in scientific works and require a dedicated study. The preservation, documentation, and restoration of modernist buildings and complexes in eastern Ukraine, especially in the Kharkiv region, require the creation of a periodisation and systematisation of buildings belonging to this glorious period of architectural development. Residential districts created in the 1920s and 1930s in Soviet Ukraine, particularly in the metropolitan Kharkiv, are objects of cultural and historical value subject to documentation and analysis. The tendency to highlight the most outstanding examples leaves out the contextual buildings, which formed the basis of the development of the residential area behind Derzhprom and created a coherent architectural and temporal background of the urban landscape of the new administrative centre of the metropolitan Kharkiv. Meanwhile, the contextual buildings created an architectural setting for more famous examples, such as the Slovo House. When studying the scientific works of Kharkiv architecture researchers, one can pay attention to the coverage of residential blocks to the west of Nauky Avenue, an area with a radial-ring structure, and the almost complete absence of research on residential blocks in the part of the district to the east of the avenue. This fact is quite unfortunate, as the architectural landscape of the blocks in this part of the residential area is notable in its spatial, functional, and stylistic structure. In addition, these blocks are rich in ‘red’ residential buildings, raised in the second half of the 1920s in various cities of Soviet Ukraine, which became a kind of visiting card of life in the Soviet Union then.